Perbedaan Tingkat Kecemasan Ibu Nifas Sebelum dan Sesudah Pemberian Hypnobreastfeeding dan Aromaterapi Lavender di RSU Ganesha - Ni Kadek Ratna Dewi; I Gusti Agung Ayu Novya Dewi; Sri Rahayu (Jurnal Riset Multidisiplin Edukasi, 2025)
The postpartum period was an important phase for the mother's recovery and adaptation to her role after giving birth. This condition was often accompanied by anxiety, which affected the mother's physical and mental health as well as her interaction with the baby. The prevalence of postpartum depression in Indonesia reached 22.4%, exceeding that of developed countries. The study aimed to analyze the anxiety levels of postpartum mothers before and after receiving hypnobreastfeeding and lavender aromatherapy at Ganesha General Hospital. This research was a pre-experimental study with a one-group pretest-posttest design using consecutive sampling. The sample size was determined using paired numerical comparative formulas, resulting in 35 respondents. Measurement was conducted using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. The study was conducted at Ganesha General Hospital from March to April 2024. The results indicated a significant decrease in anxiety levels after the intervention, from a pretest mean of 8.43 to 5.14, categorized as normal anxiety levels. Normality testing of the data using Shapiro-Wilk showed a normal distribution, thus bivariate analysis employed a Paired T Test with a p-value of 0.000 < 0.05. There was a difference in the anxiety levels of postpartum mothers before and after receiving hypnobreastfeeding and lavender aromatherapy. Postpartum mothers were expected to embrace the insights of hypnobreastfeeding and lavender aromatherapy in reducing anxiety, and future researchers were hoped to add control groups and expand the sample size.